Laboratory simulation of the influence of chromatographic effect and microbial oxidation on hydrocarbon microseepage. (29th September 2022) - Wang, Guo-Jian; Zou, Yu; Klusman, Ronald W.; Tang, Jun-Hong; Lu, Li
An experimental apparatus has been constructed with various experimental conditions to simulate the influence factors of the hydrocarbon gases microseeping from the deep reservoir to the surface. Both the chromatographic effect and the microbial oxidation effect are considered in the experiment. The results show that: the vertical hydrocarbon microseepage has the characteristics of a 'jump-over migration effect'; the coupling of a chromatographic process and microbial oxidation has less effect on the composition ratios of microseepage hydrocarbons, whereas the microbial oxidation has a large effect on the isotope values of methane; and the normal alkane and iso-alkane content of vertical microseepage show obvious differences due to the influence of chromatographic process and microbial oxidation. These experimental results may help to identify the genetic origins of the vertically migrating hydrocarbons, and thus promote the successful application of the surface hydrocarbon geochemical exploration technology. [Received: July 1, 2021; Accepted: February 23, 2022]